'Until death do us part'? Migrant wives, left-behind husbands, and the negotiation of intimacy in transnational marriages. Issue 16 (30th September 2020) - Acedera, Kristel A. F.; Yeoh, Brenda S. A.
ABSTRACT: This paper examines how migrant wives and left-behind husbands negotiate their gendered identities across the multi-layered spatialities of homeland and host society. Using a qualitative, multi-sited approach, we analyse the mutual constitution of labour migration and transnational marriages by focusing on the transnational negotiation of intimacy between Filipino migrant wives working in Singapore and Filipino left-behind husbands living in the Philippines. First, we examine how gendered ideologies rooted in notions of women as 'light of the home' and men as 'pillar of the home' shape and undergird the discourse and practice of Filipino marriages. But even as these gendered constructs travel beyond the homeland, restrictive gendered identities become increasingly untenable as women's labour migration brings about shifting power dynamics in transnational marriages. Second, drawing on the affective structures of shame and guilt, we argue that the regulation of the homeland's hegemonic gendered constructs are internalised and imbibed through 'symbolic violence'. At the same time, we also show that migrant wives and left-behind husbands find ways to navigate the liminal space of migration by rationalising gendered forms of transgression.